Antioxidant, Antimicrobial, Anti-diarrheal and Analgesic Activities of Diospyros malabarica (Desr.) Kostel (Bangladesh Pharmaceutical Journal, 2019)
The present study was designed to evaluate the antioxidant, antimicrobial, antidiarrheal and analgesic activities of methanol extract of Diospyros malabarica (Desr.) Kostel buds growing in Bangladesh. The total phenolic content of methanol extract of D. malabarica and its Kupchan fractions was determined and expressed in gallic acid equivalent (GAE). In the DPPH free radical scavenging assay, the aqueous soluble fraction of the methanol extract of D. malabarica revealed maximum free radical scavenging activity having IC50 value of 6.17 μg/ml. In antimicrobial assay, all the test samples displayed prominent antimicrobial activity against the test organisms under in vitro conditions. Among these, the carbon tetrachloride soluble fraction was found to exhibit the highest activity against Bacillus cereus, Salmonella Typhi, Salmonella Paratyphi, and Candida albicans with the zone of inhibition as 32, 30, 28 and 30 mm, respectively. In evaluation of antidiarrheal activity, the D. malabarica extracts showed significant anti-diarrheal potential in a dose dependent manner. During the evaluation of analgesic activity by radiant heat tail-flick method, the plant extract at 400 mg/kg b.w. exhibited highest elongation (373.04%) as compared to morphine (472.48%). On the other hand, in acetic acid-induced writhing test, the extract at 200- and 400-mg/kg b.w. showed 61.11 and 66.67% inhibition of writhing in mice model, respectively as compared to 68.06% inhibition produced by the standard diclofenac-Na. The findings of this study justify some of the traditional uses of D. malabarica and reveal the bioactivity of the plants. Further studies are required to isolate and identify the bioactive compounds.Bangladesh Pharmaceutical Journal 22(1): 27-33, 2019